E ancora Innovazione e Tecnologie Avanzate alla 2° Conferenza Utenti Laser Scanner Leica Geosystems - Redazione MediaGEO (GEOmedia, 2016)
The article is the second part of the report "Innovation and Advanced Technologies at the 2nd Conference User Laser Scanner Leica Geosystems" published starting from issue 5 of GEOmedia 2015. We summarize, in this article, the most relevant technologies disclosed during the conference.